Обобщение результатов испытаний горных пород на наковальнях бриджмена с целью выбора материала контейнера АВД - Виноградов, С.А.; Доценко, В.М. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
On the basis of the dimensionless analysis there was shown that the squeezing process of different
materials, partly, rocks, between flat Bridgman anvils turns out to have physical similarity to
the squeezing process of a container in the HPA of the “anvil with recess” type. The received results
allow to recommend the HPA with flat anvils as an instrument to fulfil modelling of the material’s
behaviour in the HPA with profiled anvils to chose the materials for the container fabrication.